Pengembangan Media Augmented Reality untuk Meningkatkan Kemampuan Menulis Teks Deskripsi Siswa SMP - Riski Triman Hidayat Harefa; Wety Niatri Lase; Riana Telaumbanua; Arozatulo Bawamenewi (Journal on Education, 2023)
Learning media are all tools that can be used to convey messages or information to other people, so that they are able to arouse students' thoughts, feelings, concerns and interests so that teaching activities are carried out properly. One of the technologies in education that can support the learning process is the selection of digital-based learning media, namely Augmented Reality. Augmented Reality is a technology-based learning media that can insert information into the virtual world and display it in the real world. This research was conducted to produce a product in the form of Augmented Reality media on descriptive text material in class VII SMP. The model used is a development model that goes through 4 main stages, namely the first stage of definition, the second stage of design, the third stage of development, and the fourth stage of dissemination. Data collection techniques in this study were questionnaires and validation sheets. This study obtained the results of due diligence with a percentage of 93% by material experts, 92% by linguists and 91% by media/design experts with very feasible criteria. Student responses of 90% belong to very practical criteria.